Different combination of behavior change interventions and frequency of interpersonal contacts are associated with infant and young child feeding practices in Bangladesh, Ethiopia, and Viet Nam - Kim, Sunny S.; Nguyen, Phuong Hong; Tran, Lan Mai; Alayon, Silvia; Menon, Purnima; Frongillo, Edward A. (American Society for Nutrition, 2020)
Background Social and behavior change communication interventions are integral to improving dietary and care practices, but evidence on the impact of the combination and intensity of these interventions in different contexts is scarce. Objective We examined the extent of and factors associated with intervention exposure: interpersonal communication (IPC) alone or with other interventions (i.e., mass media, community mobilization, or nutrition-sensitive agricultural activities); number of and factors associated with IPC contacts; and combinations of intervention components and number of contacts associated with infant and young child feeding (IYCF) practices.